Influência da precipitação pluviométrica na reflectância espectral da água do reservatório Passo Real, RS - Barbieri, Daniela Wancura (2012)
The water s reflectance related to pluviometric rate allows a characterization of natural and severe changes on the water s metabolism. Accordingly, the purpose of this research is to establish a relation between pluviometric rates and the changes on the water s reflectance values in Passo Real reservoir, localized on the north of Rio Grande do Sul. As methodology 11 MODIS (Moderate Resolution Imaging Spectroradiometer) images from NASA s Image Catalog were used to compose one hydrological year. The rainfall data are originating from the Civilian Defense Department of the state of Rio Grande do Sul, adding up to 31 stations of pluviometric gatherings to the research. The water s transparency data (Total of Solids in Suspension) (TSS) were acquired from 31 sample points during 8 field works. The analysis has considered the accumulation of rainfall in the period of 5, 10, 15, 20, 25, and 30 days before the satellite s passage. Red band (648nm) reflectance data were used in 3 compartments of the reservoir which represent the main spots of gathering: Ingaí river, Jacuí-Mirim river and Jacuí river. The limnological data, rainfall and water s reflectance were added to verify their relations. It has been verified that the year of 2009 presented distinct periods as the dry rain regimen from January to July and rainy from August to December. The reflectance rates were from 0,28 to 2,05% in the dry period while from 0,44 to 3,27% in the rainy period. The medium transparency values from the Secchi Disc (SD) were 1,2 m. However in the dry period, the transparency was 1,7m and in the rainy period 0,7 m. The TSS s minimum value was 0,5 mg/L and maximum of 31 mg/L in the dry period and from 1 to 33 mg/L in the rainy period. The lower TSS s concentrations were gathered in the month of April 1mg/L when the lower rainfall rates were registered. Nonetheless, the highest concentration was registered in October (33 mg/L) when the highest rainfall rates were registered in the water basin (224mm). It has been verified meaningful relations to the water s reflectance and to the rain preceding the sensor s passage to the rain s accumulated value during 20 preceding days to the satellite s passage was what presented the correlation of 0,88 to the reflectance of the sector of Jacuí river and 0,83 to the sector of Jacuí-Mirim river. The aquatic compartment defined by Ingaí river had the best correlation (0,78) when the accumulated of rain was of a period of 25 days. Therefore, the MODIS images register the rains in a period of 20 days before the satellite s passage. Specifically in the compartment of Ingaí river, this effect occurs in a period of 25 days.